The Effect of Chronic Renal Failure on Thyroid Hormones - K. Ali, Layla (Iraqi Journal of Pharmaceutical Sciences, 2017)
Chronic renal failure (CRF) affects thyroid function in multiple ways, including low circulating thyroid hormone concentration, altered peripheral hormone metabolism, disturbed binding to carrier proteins, possible reduction in tissue thyroid hormone content, and increased iodine store in thyroid glands.The target of study is to find a relationship between chronic renal failure and thyroid function.In addition, we tried to study the effect of CRF on serum creatinine dependent on the level of thyroid hormones (T3 and T4) and thyroid stimulating hormones(TSH). Forty patients with chronic renal failure (20 male, 20 female) were enrolled in this study in addition to forty healthy individual as control group (20 male, 20 female). The age ranged from (25 -65) years. T4, T3, TSH, urea, uric acid and creatinine were measured in each of the two groups. The results revealed statistically significant reduction in T3 and T4 while there is elevation in TSH, urea,uric acid and creatinine in the patients group compared to the control group. Key word : Chronic Renal Failure,Thyroid Hormones.